TRPV4 affects visual signals in photoreceptors and rod bipolar cells - Long, Ye; Kozhemyakin, Maxim; Wu, Samuel M.; Pang, Ji-Jie (Frontiers in Cellular Neuroscience, 2024)
Mechanical sensitive channels expressed in mammalian retinas are effectors of elevated pressure stresses, but it is unclear how their activation affects visual function in pressure-related retinal disorders. This study investigated the role of the transient potential channel vanilloid TRPV4 in photoreceptors and rod bipolar cells (RBCs) with immunohistochemistry, confocal microscopy, electroretinography (ERG), and patch-clamp techniques. TRPV4 immunoreactivity (IR) was found in the outer segments of photoreceptors, dendrites and somas of PKCalpha-positive RBCs and other BCs, plexiform layers, and retinal ganglion cells (RGCs) in wild-type mice. TRPV4-IR was largely diminished in the retinas of homozygous TRPV4 transgenic mice. Genetically suppressing TRPV4 expression moderately but significantly enhanced the amplitude of ERG a-and b-waves evoked by scotopic and mesopic lights (0.55 to 200 Rh*rod -1 s -1 ) and photopic lights (10^5 -10^6 Rh*rod -1 s -1 ) compared to wild-type mice in fully dark-adapted conditions. The implicit time evoked by dim lights (0.55 to 200 Rh*rod -1 s -1 ) was significantly decreased for b-waves and elongated for a-waves in the transgenic mice. ERG bwave evoked by dim lights is primarily mediated by RBCs, and under voltage-clamp conditions, the latency of the light-evoked cation current in RBCs of the transgenic mice was significantly shorter compared to wild-type mice. About 10% of the transgenic mice had one eye undeveloped, and the percentage was significantly higher than in wild-type mice. The data indicates that TRPV4 involves ocular development and is expressed and active in outer retinal neurons, and interventions of TRPV4 can variably affect visual signals in rods, cones, RBCs, and cone ON BCs.